Digital Media and Arabic Language: The Relevance of Digital Media in Arabic Language Learning - M. Anwar, Falikhah Ramdani; Falikhah Ramdani; Dhiyaul Millah; Choirunnisa Marwa Nurul Amin (TOFEDU: The Future of Education Journal, 2025)
<!--StartFragment--> This study talks about learning Arabic through digital methods because we’re now living in a tech-driven world, and it’s important for both students and teachers to adapt to these changes.The purpose of this study is to explore how Arabic can be taught digitally, what the benefits and challenges are, and how to overcome those challenges. The research was done using a literature review method by collecting and analyzing sources like journals, books, and academic articles from the last five years, using the theory of constructivism, which focuses on students being active in building their own knowledge. The results show that digital Arabic learning can make the process more flexible, engaging, and effective, but there are still issues like limited access to technology, lack of digital skills among teachers and students, and school curriculums that haven’t fully adapted yet. In conclusion, digital Arabic learning has great potential to improve education quality if supported with teacher training, proper facilities, and collaboration between different parties to create a better learning system. <!--EndFragment-->